(untitled) (Research, Society and Development, 2024)
This research aims to gather and analyze the factors responsible for triggering the symptoms of Burnout Syndrome in health professionals (doctors and nurses) who work in Intensive Care Units (ICU) across the country. We aim to identify the characteristic symptoms of Burnout Syndrome in doctors and nurses who work in an ICU environment and track the reasons identified as causing this type of illness. The methodology used in this study is based on an integrative literature review in which it is based on research, screening, compilation and analysis of previously published studies that deal with the topic in question. 11 studies were selected, all cross-sectional, which included health professionals from various regions of Brazil. The most recurrent symptoms identified were emotional exhaustion, depersonalization, lack of professional fulfillment, work overload, alcoholism, muscle pain, mood changes and poor sleep quality. Highlighted risk factors include high workload, lack of control over work, and low support from colleagues. Other factors, such as inadequate physical conditions and constant pressure, have also been identified as causing the syndrome. It can be concluded that the characteristic clinical manifestations of this condition are multifaceted and significantly impact the mental health and well-being of these professionals. The importance of prevention and intervention strategies was also highlighted, highlighting the need for adjustments in working conditions, such as reducing working hours, improving wages, and implementing practices such as quality sleep and regular physical activities to mitigate the effects of stress.